Tissue Oxygen Saturation and Finger Perfusion Index in Central Hypovolemia. Issue 4 (April 2015) - Høiseth, Lars Ø.; Hisdal, Jonny; Hoff, Ingrid E.; Hagen, Ove A.; Landsverk, Svein A.; Kirkebøen, Knut A.
<x xml:space="preserve">Abstract</x> Objectives: Tissue oxygen saturation and peripheral perfusion index are proposed as early indirect markers of hypovolemia in trauma patients. Hypovolemia is associated with increased sympathetic nervous activity. However, many other stimuli, such as pain, also increase sympathetic activity. Since pain is often present in trauma patients, its effect on the indirect measures of hypovolemia needs to be clarified. The aim of this study was, therefore, to explore the effects of hypovolemia and pain on tissue oxygen saturation (measurement sites: cerebral, deltoid, forearm, and thenar) and finger photoplethysmographic perfusion index. Design: Experimental study. Setting: University hospital clinical circulation and research laboratory. Subjects: Twenty healthy volunteers. Interventions: Central hypovolemia was induced with lower body negative pressure (–60 mm Hg) and pain by the cold pressor test (ice water exposure). Interventions were performed in a 2 × 2 fashion with the combination of lower body negative pressure or not (normovolemia), and ice water or not (sham). Each subject was thus exposed to four experimental sequences, each lasting for 8 minutes. Measurements and Main Results: Measurements were averaged over 30 seconds. For each person and sequence, the minimal value was analyzed. Tissue oxygenation in all measurement sites and finger perfusion index were reduced during hypovolemia/sham compared with normovolemia/sham. Tissue oxygen saturation (except cerebral) and perfusion index were reduced by pain during normovolemia. There was a larger reduction in tissue oxygenation (all measurement sites) and perfusion index during hypovolemia and pain than during normovolemia and pain. Conclusions: Pain (cold pressor test) reduces tissue oxygen saturation in all measurement sites (except cerebral) and perfusion index. In the presence of pain, tissue oxygen saturation and perfusion index are further reduced by hypovolemia (lower body negative pressure, –60 mm Hg). Thus, pain must be considered when evaluating tissue oxygen saturation and perfusion index as markers of hypovolemia in trauma patients.